The Effect of the Blended Learning Model Based on the Nearpod Application on Students' Physics Interest and Learning Outcomes at MAN - Cahyani, Vandaria Dewi; Maryani, Maryani; Nuraini, Lailatul (Department of Physics Education, Universitas Mataram, 2024)
This research aims to determine the effect of a blended learning model based on the application of Nearpod on students' interest and learning outcomes in physics at one of the secondary schools in Jember. This research is a type of experimental research that uses a post-test only control group design. The population of this study were students of class XI MIPA and XI BIC. Sampling used a random sampling technique, so that XI BIC 2 students were obtained as a control group implementing the conventional learning model and XI MIPA 1 as an experimental group implementing blended learning based on the Nearpod application. The instrument used is a physics student interest questionnaire which consists of 4 indicators and a post test in the form of a multiple-choice test which refers to students' cognitive abilities to remember (C1), understand (C2), apply (C3), analyze (C4), evaluate (C5), and create (C6). Questionnaire data and post test data regarding the influence of blended learning based on the Nearpod application on students' interest in learning and physics learning outcomes will be tested for homogeneity. If a significance value >0.05 is obtained, questionnaire and post test data for the control class and experimental class were normally distributed. Interest data and physics learning outcomes were analyzed using parametric statistics, namely the Independent Sample T-test. Based on the hypothesis testing criteria, H0 is rejected (Ha is accepted) if the sig value is <0.05, meaning that there is an influence of the Nearpod application-based blended learning model on student physics interest. Meanwhile, in the physics learning outcome test, students got the sig value of <0.05, which means that Ha is accepted, meaning that there is an influence of the Nearpod-based blended learning model on student physics learning outcomes. The application of the blended learning model based on the Nearpod application has a significant effect on students' interest and learning outcomes in physics.